Rb-Sr mineral isochron ages of metamorphic rocks around Syowa Station and from the Yamato Mountains, East Antarctica - Shibata, Ken; Yanai, Keizo; Shiraishi, Kazuyuki (1985)
P(論文) Rb-Sr mineral isochron ages were determined for three metamorphic rocks around Syowa Station and from the Yamato Mountains, eastern Queen Maud Land. The Rb-Sr isotopic data demonstrate that the complete Sr isotopic homogenization occurred among K-feldspar, plagioclase, biotite and whole-rock, and define isochron ages of 482.5±9.5,468.9±7.8 and 493.3±4.5 Ma for rocks from Syowa Station, Skarvsnes and the Yamato Mountains, respectively. These ages probably represent the time of cooling after the regional metamorphism or granite intrusion. K-Ar age determinations on three metamorphic rocks give biotite and hornblende ages of 469±14,480±15 and 483±15Ma, and 502±15Ma, respectively. departmental bulletin paper